Zika virus Concern and Preventative Behaviors During Pregnancy: Analysis of 2017 Georgia Pregnancy Risk Assessment Monitoring System data - Priya Nair; Christine Stauber (Georgia Southern University, 2021)
Background: Zika virus infection can cause severe health complications in pregnant women such as microcephaly and other congenital anomalies in the developing fetus but it can be prevented. It is imperative to develop an understanding of concern about Zika virus among pregnant women as this can influence their Zika virus preventative behaviors. The purpose of this study was to gain an understanding of Zika virus concern among women in Georgia with live births in 2017 and to examine the frequency of condom use among those who were sexually active during their most recent pregnancy. Methods: This cross- sectional study used secondary data collected by Georgia Pregnancy Risk Assessment Monitoring System in 2017. Descriptive analyses were performed on variables of interest. Chi squared tests examined associations between level of concern about Zika virus and socio-demographic variables. Results: A total of 955 women (age range 18-45) completed the survey. Less than half of the women (n =418,47.4%) reported they were concerned about Zika virus. Consistent use of condoms was not associated with the level of concern of Zika virus. Among the women, those of Hispanic race/ethnicity were more likely to consistently use condoms during their most recent pregnancy (Adjusted Odds Ratio = 11.37; 95%CI: 3.95-32.81) when compared to Non-Hispanic white women, and this association was found to be statistically significant (p<0.0001). Conclusion: Consistent use of condoms by sexually active women in Georgia during pregnancy appears to vary by race/ethnicity for these women. Findings of this study point to opportunities for engagement on Zika virus awareness and help with refining risk messaging for prevention of Zika virus (or other diseases of global concern) to pregnant women